PENGEMBANGAN MODUL LITERASI NUMERASI BERBASIS BUDAYA BETAWI UNTUK KELAS V SEKOLAH DASAR - Anggoro, Inggit Dwi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to develop and determine the feasibility of a Betawi culture-based numeracy literacy module for fifth grade elementary school students. This research is based on the low numeracy literacy skills of students and the lack of contextual teaching materials. This research uses the Research and Development (R&D) approach with the ADDIE development model. Data collection techniques used included observation, interviews, and questionnaires to teachers and students. The resulting product is in the form of a module “Senangnya Belajar Matematika melalui Jelajah Betawi”. This module was tested by three experts (media, material, and language) and users. The feasibility test results showed that the module obtained an average percentage of 96.3% from experts and 99.12% from users with the category “very feasible”. This module integrates Betawi culture which is depicted through the context of numeracy questions and activities, different from other local culture modules which generally only insert traditional elements visually. This module is also designed to encourage students' exploration of local culture in mathematics learning, in line with the Merdeka Curriculum. Thus, this module can be used as an alternative contextual and innovative learning media to improve the numeracy literacy skills of elementary school students.